Extreme emulsification: formation and structure of nanoemulsions - Mason, T.G.; Graves, S.M.; Wilking, J.N.; Lin, M.Y. (Condensed Matter Physics, 2006)
Nanoemulsions are metastable dispersions of nanodroplets of one liquid that have been ruptured by shear in another immiscible liquid. The ruptured droplets are stabilized against subsequent coalescence by a surfactant. Because the nanodroplets do not form spontaneously, as they can in lyotropic “microemulsion” phases, the structure of nanoemulsions is primarily dependent on the history of the applied shear stresses relative to the interfacial restoring stresses. By applying extremely high shear rates and controlling the composition of the emulsion, we have been able to rupture microscale droplets down to diameters as small as 30 nm in a microfluidic process that yields bulk quantities suitable for commercial production. Following ultracentrifugal fractionation to make the droplets uniform, we study the structure of these emulsions using small angle neutron scattering (SANS) at dilute and concentrated volume fractions. We contrast the structure of a concentrated nanoemulsion with the structure factor of hard spheres at a similar volume fraction.